VALORES DE REFERÊNCIA PARA AS CLASSES DE RUÍDO PREVISTAS NA NORMA NBR 15575 - Brito, Adriana; Sales, Elisa Morandé; Akutsu, Maria; Aquilino, Marcelo de Mello (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Brazilian Standard NBR 15575 establishes criteria for sound insulation of the building envelope according to the value of the environmental noise class. However, there is only a qualitative description of the noise classes. The objective is to propose values for the noise classes considering also the criteria presented in the Brazilian Standard NBR 10152 for sound insulation of the building envelope. So, reference values were calculated for the sound pressure level of the noise classes for the requirements of bedrooms. In order to verify if the values established for the noise classes correspond to the characteristics described in the Standard NBR 15575, computational simulations of the urban noise propagation were performed, considering typical situations observed in São Paulo city. The suggested reference values for the noise are presented considering three classes.